2022
DOI: 10.1371/journal.pone.0264222
|View full text |Cite
|
Sign up to set email alerts
|

How does inquisitiveness matter for generativity and happiness?

Abstract: Inquisitiveness (curiosity & acceptance to something and someone different) is the main engine for one person to initiate some relation, and the literature has established that maintaining nice relationships with friends, family and general others contributes to generativity and happiness. However, little is known about how generativity and happiness are characterized by inquisitiveness. We hypothesize that inquisitiveness is a fundamental determinant for generativity and happiness, empirically examining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 111 publications
(159 reference statements)
0
12
6
Order By: Relevance
“…Second, GCS-R has a positive effect on the participants' SH at 1% significance only in model 1. Previous studies with adults find the effect of generativity on subjective happiness statistically significant in a robust manner [11,49,70], while this study with children finds the effect statistically insignificant, except for model 1. Areas exhibit 1% and 5% statistical significance with a negative sign in models 1 to 4, implying that the urban participants tend to decrease their SH by −0.834 * −0.698, as compared with the non-urban participants.…”
Section: Plos Onecontrasting
confidence: 75%
See 2 more Smart Citations
“…Second, GCS-R has a positive effect on the participants' SH at 1% significance only in model 1. Previous studies with adults find the effect of generativity on subjective happiness statistically significant in a robust manner [11,49,70], while this study with children finds the effect statistically insignificant, except for model 1. Areas exhibit 1% and 5% statistical significance with a negative sign in models 1 to 4, implying that the urban participants tend to decrease their SH by −0.834 * −0.698, as compared with the non-urban participants.…”
Section: Plos Onecontrasting
confidence: 75%
“…The maximum possible range is between 10 and 50 and is calculated as the sum of the scores on the inquisitiveness questions. This subscale reliably measures the influence of people's behaviors and attitudes in many vital contexts [70,85].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the coefficients of determination in our multiple regression analyses were relatively small. Prior research has identified agentic and communal goal attainment [ 23 ] and psychological well-being [ 17 , 24 ] as being strongly associated with generativity. Therefore, it is necessary to reevaluate our findings after controlling for these variables.…”
Section: Discussionmentioning
confidence: 99%
“…They find inquisitiveness as essential for reaching a conclusion that is not bounded by individuals' beliefs. Hirose and Kotani [70] also demonstrate that inquisitiveness positively correlates with how people enhance their generative concern and happiness by conducting questionnaires with 400 Japanese. Overall, inquisitiveness is an engine of increasing the motivation and behaviors in some situations, triggering communications with others and interactions with unfamiliar environments [59,[71][72][73].…”
Section: Introductionmentioning
confidence: 99%